Analysis of Articles on Education and Instructional Technologies (Scopus) - Tavukcu, Tahir; Kalimullin, Aydar M; Litvinov, Aleksandr V.; Shindryaeva, Natalya N.; Abraukhova, Valentina; Abdikeev, Niyaz M. (International Journal of Emerging Technologies in Learning (iJET), 2020)
It is an indisputable fact that technology is a part of our lives. It is known that research and education technologies are concentrated. By examining the articles and dissertations published in the field, the scope, strengths and weaknesses of the studies were determined. An important gap has been filled in to guide researches what kind of studies may be needed in the future. Many studies for this purpose were found in the literature. However, since similar studies dealing with educational technologies are outdated, this study is considered important in terms of gathering current research trends and results. The aim of this study is to analyse the articles published in the Scopus database on educational technologies and instructional technologies, thematically and methodologically. The study was designed by adopting a case study from qualitative research models. The sample has not been determined for postgraduate dissertations to be included in the study, and it was aimed to reach the whole universe. In this context, all articles have been accessed through the library system of the university in the Scopus database included. The keywords ‘educational technologies’ and ‘instructional technologies’ were used in the article search. The document types have been examined by year, by country, by authors, by field research and by place of publication.